Synthetic Financial Data: A Case Study Regarding Polish Limited Liability Companies Data - Aleksandra Szymura (Ekonometria)
Aim: The aim of this article is to present and evaluate the concept of synthetic data. They are completely new, artificially generated data, but keep the statistical properties of real data. Due to the statistical similarity with real data, they can be used instead of them. This action allows data to be shared externally while guaranteeing their privacy.